2005
DOI: 10.2747/0272-3638.26.5.365
|View full text |Cite
|
Sign up to set email alerts
|

The Reinvention of Public Green Space

Abstract: Much attention has been paid to preserving land at the urban fringe, and to the negative effects of sprawl and its costs. There is increasing recognition that enhancing green, public open spaces in cities provides a strategy to make those cities more sustainable, more livable, and more equitable. This involves a new approach to public spaces that integrates infrastructure needs, takes equity into account, and reexamines the range of uses public spaces offer. We consider the potential for urban greening through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 25 publications
1
63
0
1
Order By: Relevance
“…Age, gender, education level, income, retirement status, residential neighbourhood and length of stay tend to influence peoples' perception [16,91,[95][96][97]. Varied responses to nature have also been noted between communities varying in race or class [90,98]. However, Qureshi et al [97] in study in Karachi found no impact of age group or gender on the behavioural pattern of respondents.…”
Section: Main Uses Of Green Spaces As Ascertained By Different Populamentioning
confidence: 90%
“…Age, gender, education level, income, retirement status, residential neighbourhood and length of stay tend to influence peoples' perception [16,91,[95][96][97]. Varied responses to nature have also been noted between communities varying in race or class [90,98]. However, Qureshi et al [97] in study in Karachi found no impact of age group or gender on the behavioural pattern of respondents.…”
Section: Main Uses Of Green Spaces As Ascertained By Different Populamentioning
confidence: 90%
“…As a critical constituent of urban landscape and infrastructure, it has been increasingly acknowledged and widely documented in the literature that urban green spaces could effectively counteract various negative environmental impacts associated with urbanization (Kabisch & Haase, 2013;Swanwick, Dunnett, & Woolley, 2003) and underpin social and ecological functioning and human well-being in urban environs (Barbosa et al, 2007;Pincetl & Gearin, 2005;Tzoulas et al, 2007;van Zoest & Hopman, 2014). Despite a broad consensus about the importance and value of urban green spaces (Haq, 2011;Villanueva et al, 2015), the dynamics of their provision remains controversial and elusive.…”
Section: Introductionmentioning
confidence: 98%
“…In relation to cormorants, site users will continue to influence the spatial extent of the colonies as cormorants will not likely expand close to areas of the Spit used extensively by humans. Therefore, we should not separate humans further, with a laissez-faire approach, from the already sparse nature areas in urban settings (see Pincetl and Gearin 2005), but focus instead on education (Adams 2005;Teillac-Deschamps et al 2009) and experiential engagement (Gill et al 2009;Gruenewald 2003). Ecological change, while sometimes aesthetically undesirable, is an inevitable outcome, and examples of species modifying their landscape can be used in experiential learning to explore this fundamental concept in ecology.…”
Section: Discussionmentioning
confidence: 97%